Impedance measurements on an engineered cementitious composite: A critical evaluation of testing protocols. (December 2018) - Suryanto, Benny; Takaoka, Hideaki; McCater, W. John; Saraireh, Danah; Taha, Hussameldin
Highlights: A critical evaluation of electrical property measurements on cementitious materials. Identification of key factors which influence testing procedures/protocols. A dual bulk-arc response observed in the Nyquist format. Influence of contacting medium detectable across the entire frequency range. Interfacial phenomena at the electrode/specimen contact region highlighted. Abstract: An end-to-end (two-point) electrical measurement technique is traditionally employed in evaluating the bulk resistivity of hardened cementitious materials. This testing methodology is critically evaluated by studying the electrical impedance of an engineered cementitious composite (ECC), using cuboidal specimens with four different dimensions viz. 50 mm, 70 mm, 100 mm and 150 mm. In the present work, the impedance response (in the form of Nyquist plots) of the ECC specimens was measured over the frequency range 1 Hz–10 MHz via two external plate-electrodes placed at opposite faces of each specimen. A conductive gel, or saturated, synthetic sponges inserted between the plate/specimen interface were used as the electrode-specimen contacting medium. It is shown that the sponge contacting medium introduced a spurious response which was detectable across the entire frequency range and was particularly evident in specimens with smaller electrode contact area and in specimens with air-voids present on the contact surface. This effect was considerably reduced when either the conductive gel or sponges saturated with highly-conductive liquid was used. It is also shown that the true bulk resistivity of the material, identified from the Nyquist plot, can be evaluated by subtracting the resistivity of the sponge itself from the bulk resistivity of the ECC with the sponges present. Benchmarking studies were also undertaken on specimens with an embedded electrode arrangement.